Garbage Is Good to Think With: The Interplay of Civic Activism and Judicial Intervention in Shaping Bangalore’s Solid Waste Management Policies - Christine Lutringer; Shalini Randeria (Revue Internationale de Politique de Développement)
In 2012, Bangalore was the first Indian metropolitan city to adopt a comprehensive solid waste management policy based on decentralisation. This article examines the interplay between middle-class environmental activism and judicial interventions, an interplay that shaped the making of this municipal policy. We argue that the production and implementation of public policy regarding a key service provision like waste collection and disposal is no longer the domain of elected city officials or the city administration alone. The provisions of the policy are related instead to the nature of judicial activism as well as to the specificities of the policy community that came together following the breakdown of the waste management system. Bangalore evinces a constellation of actors and factors conducive to environmental activism driven by civic sense and idealism, as much as by economic interests and the desire to implement technological solutions. We delineate, on the one hand, some of the strategies of these actors, at the level of households and gated communities, for initiating changes in waste segregation, and—on the other—some mechanisms put in place to foster public participation and deliberative decision-making. We show why activism regarding and court orders on waste in Bangalore were unusual in going beyond the garbage problems of the city to address larger (environmental and social) rural–urban linkages too.